Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection in an Italian cohort in Marche Region, Italy - De Santi, Mauro; Diotallevi, Aurora; Brandi, Giorgio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The COVID-19 is an infectious disease caused by the novel coronavirus SARS-CoV-2, declared a public health emergency by the World Health Organization. In this study, we evaluated the seroconversion of SARS-CoV-2 antibodies to find predictors of infection in terms of symptoms, health status, and professions. Methods: Serological samples of 341 volunteers in a cohort in Marche Region, Italy, were analyzed for the presence of IgM and/or IgG immunoglobulins specific for the SARS-CoV-2. Contextually, an anamnestic questionnaire was administered. The binary logistic regression analysis was used to find the predictors of seroconversion. Results: Forty-nine subjects (14.4 %) were found positive, without significant differences between gender and age groups. The predictors identified inside the variable categories “symptoms,” “risk factors” (smoking habit and established pathologies), and “professions” were the loss of taste and smell (OR, 8.563), cardiovascular diseases (OR, 2.912), and policeman profession (OR, 3.875), respectively. Conclusions: Although the limited number of subjects recruited in this study, our results could give important findings to be considered for planning preventive strategies in the view of the next COVID-19 waves.